2021
DOI: 10.1038/s41598-021-91484-w
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of nitrogen-grafted copper-gallic acid for enhanced methylene blue removal

Abstract: Nitrogen-grafting through the addition of glycine (Gly) was performed on a metal- phenolic network (MPN) of copper (Cu2+) and gallic acid (GA) to increase its adsorption capacity. Herein, we reported a one-step synthesis method of MPN, which was developed according to the metal–ligand complexation principle. The nitrogen grafted CuGA (Ng-CuGA) MPN was obtained by reacting Cu2+, GA, and Gly in an aqueous solution at a molar ratio of 1:1:1 and a pH of 8. Several physicochemical measurements, such as Fourier tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Auramine O (AO) and methylene blue (MB) are the most widely used dyes in the industry. Respiratory irritation, teratogenicity, and carcinogenicity in humans are the main drawbacks of poisoning by these compounds 6 , 7 . Moreover, the presence of these dyes in water sources would lead to blocking the light penetration into the water, disruption of photosynthesis, and destruction of the aquatic ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Auramine O (AO) and methylene blue (MB) are the most widely used dyes in the industry. Respiratory irritation, teratogenicity, and carcinogenicity in humans are the main drawbacks of poisoning by these compounds 6 , 7 . Moreover, the presence of these dyes in water sources would lead to blocking the light penetration into the water, disruption of photosynthesis, and destruction of the aquatic ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…The band around 1200 cm −1 was assigned to the stretching vibrations of C–O in polyols, 30,31 and the one at 1030 cm −1 was due to the C–O–C bending mode. 32 The band around 870 cm −1 was the acid group of the out-of-plane bending of the O–H. 30 The C–H out-of-plane bending of the phenyl group was observed at 760 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Comparison between the results of other studies confirms the effect of acrylic acid hydrogels containing photocatalytic nanoparticles prepared in this study. For example, Santoso et al showed that with increasing the pH of the environment, the rate of absorption and removal of methylene blue increased [23]. They attributed this effect to creating negative charges in the alkaline environment on the adsorbent and increasing the adsorption of MB.…”
Section: Eds Analysismentioning
confidence: 99%